Micro credentials as tools for self-directed learning in social security / Mohd Zaki Awang Chek, Isma Liana Ismail - Awang Chek, Mohd Zaki; Ismail, Isma Liana (2024)
Micro-credentials are emerging as potent tools for self-directed learning, particularly in the complex arena of social security. Micro-credentials are rapidly becoming vital tools for self-directed learning, especially in the complex domain of social security. This educational approach simplifies complex information into manageable, modular courses, enabling individuals to effectively understand and plan their social security benefits. These courses are meticulously designed using Robert Gagné's Nine Events of Instruction, ensuring a systematic learning experience that enhances understanding and retention. Each course is developed to address specific learning outcomes, from basic awareness to sophisticated financial strategies, ensuring relevance and depth. The innovation of this micro-credential system lies in its high degree of customization and a robust digital badge certification system. This system recognizes and visually represents the learner's progress, serving as a motivational and verifiable record of achievement. The design of the micro-credentials prioritizes user-friendliness and accessibility, with courses available through a dedicated web-based platform and mobile application—UFuture, an official digital learning platform of Universiti Teknologi MARA (UiTM). This platform facilitates interactive learning through the integration of dynamic content, including interactive simulations and real-life case studies, which are crucial for applying theoretical knowledge in practical settings. Ultimately, the purpose of these micro-credentials is to demystify the intricacies of social security, thereby enhancing financial literacy and preparedness among individuals. This is particularly vital for fostering informed decision-making within the community, as the landscape of social security becomes increasingly complex. By providing accessible, structured, and engaging learning opportunities, the micro-credential system not only empowers individuals but also prepares a well-informed citizenry capable of navigating the challenges of modern social security systems.